Pendekatan Jelajah Alam Sekitar (JAS): Dampaknya terhadap Aktivitas dan Hasil Belajar Kognitif Siswa SMP - Sukarman Hadi Jaya Putra (Journal of Natural Science and Integration, 2021)
ABSTRACTThis study aims to determine the effect of the Surrounding Nature Exploration Approach (JAS) on the activity and learning outcomes of seventh grade students of Muhammadiyah Waipare Junior high school on the concept of classification of living things. The method used is a quasi-experimental design with a noneequivalent control grub design. The population in this study were all 7th grade students of Muhammadiyah Waipare Junior high school. The sample in this study was class VII C totaling 21 students as the experimental class and class VII D totaling 20 students as the control class. The sampling technique used was purposive sampling. The analysis of the instrument trial includes the validity test, reliability test, difficulty level, discriminatory power test. The results of the instrument trial analysis showed that all instruments were feasible to use. Data analysis techniques include normality test, homogeneity test and hypothesis testing. The results of the normality test showed that the distribution of learning outcomes was normal and the results of the homogeneity test showed that the variance of the research data was homogeneous. The t test analysis obtained a significance value of <0.05, namely (0.000 <0.05). The conclusion is a significant effect of the learning model for exploring the environment (JAS) on the learning outcomes of class VII Muhammadiyah Waipare Junior high school on the concept of classification of living things. Also the results showed that students were very active in participating in learning by using the environmental exploration learning model (JAS) on the concept of classification of living things. This is indicated by the analysis of student activity of 81.77.Keywords: explore the surrounding nature (JAS), activity, learning outcomes.ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh Pendekatan Jelajah Alam Sekitar (JAS) terhadap keaktifan dan hasil belajar siswa kelas VII SMP Muhammadiyah Waipare pada konsep klasifikasi makhluk hidup. Metode yang digunakan adalah quasi exsperimental design dengan desain Nonequivalent control grub design. Populasi dalam penelitian ini adalah seluruh siswa kelas VII SMP Muhammadiyah Waipare. Sampel pada penelitian ini adalah kelas VII C berjumlah 21 siswa sebagai kelas eksperimen dan kelas VII D berjumlah 20 siswa sebagai kelas kontrol. Teknik penentuan sampel menggunakan teknik purposive sampling. Analisis uji coba instrumen meliputi uji validitas, uji reliabilitas, tingkat kesukaran, dan uji daya pembeda. Hasil analisis uji coba instrumen menunjukkan bahwa semua instrumen layak untuk digunakan. Teknik analisis data meliputi uji normalitas, uji homogenitas dan uji hipotesis. Hasil uji normalitas menunjukkan bahwa sebaran variabel hasil belajar adalah normal dan hasil uji homogenitas menunjukkan varians data penelitian homogen. Analisis uji t diperoleh nilai signifikansi < 0,05 yaitu (0,000<0,05) sehingga dapat disimpulkan terdapat pengaruh yang signifikan model pembelajaran Jelajah Alam Sekitar (JAS) terhadap hasil belajar kognitif siswa kelas VII SMP Muhammadiyah Waipare pada konsep klasifikasi makhluk hidup. Hasil penelitian menunjukkan bahwa siswa sangat aktif mengikuti pembelajaran dengan menggunakan model pembelajaran Jelajah Alam Sekitar (JAS) pada konsep klasifikasi makhluk hidup. Hal ini ditunjukkan oleh analisis keaktifan siswa sebesar 81,77.Kata kunci: jelajah alam sekitar(JAS), keaktifan, hasil belajar